Præsten og Loke. Grundtvigs apologetiske dialog i “Om Christendommens Sandhed” - Nørager, Troels (Grundtvig-studier, 2012)
Præsten og Loke: Grundtvigs apologetiske dialog i “ Om Christendommens Sandhed”[The Pastor vs. Loke: Grundtvig ’s apologetic dialogue in his “ On the truth of Christianity ”]By Troels Nørager Due to the fact that Grundtvig propagated a basically pre-modern conception of Christianity, apologetics constitute an integral part of his theological writings. So far, however, Grundtvig’s apologetic discourse (and its strategies) has not received the scholarly attention that it deserves. This article takes as its test case a rather lengthy (ca. 40 pages) dialogue, which Grundtvig inserted into his major apologetic work, “ On the truth of Christianity”. The dialogue features a true Christian minister (Grundtvig himself) and his adversary, “ Loke”, a representative of contemporary rationalist-deist Christianity. It is demonstrated how the themes of the dialogue cluster around the Apostolic Creed, thus reflecting Grundtvig’s theological turn dating from 1825. In particular, the focus is on Grundtvig’s pervasive (but, alas, less than persuasive) use of principium contradictionis as his major apologetic tool. It is demonstrated that there remains in Grundtvig an unresolved tension between the inherent epistemological nature of this principle and Grundtvig’s desire to employ it to bolster his own exclusively theological (and ontological) concept of truth.